Penyuluhan Fisioterapi dalam Upaya Memperkenalkan Keluhan Nyeri Leher pada Petani Penyadap Karet di Desa Sirap - Geofani Nispuan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Rubber Farmers are one type of work that can be at risk of experiencing occupational diseases. The habit of standing for a long time, looking up for a long time, lifting heavy loads, long working hours can certainly affect the possibility of musculoskeletal disorders. Neck pain is one of the disorders. A study shows the prevalence of musculoskeletal pain in the neck in the community for 1 year is 40% and this prevalence is higher in women. Then, the prevalence of musculoskeletal pain in the neck area in workers is between 6-76% and it turns out that women are also more dominant than men 10. Musculoskeletal complained of by rubber farmers and can have a negative impact on farmers on the quality of their work. The method used is providing counseling on neckpain with leaflets as a promotional media as well as pretests and post-tests to assess the level of knowledge and understanding of farmers on complaints of neck pain. The results of this study indicate an increase in farmers' understanding regarding the prevention and treatment of neck pain in the right way.